2014
DOI: 10.1021/ml5000405
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New RXRα Antagonist Targeting the Coregulator-Binding Site

Abstract: Retinoid X receptor-alpha (RXRα) is implicated in the regulation of many biological processes and also represents a unique intracellular target for pharmacologic interventions. Efforts on discovery of small molecules targeting RXRα have been primarily focused on the molecules that bind to its classical ligand-binding pocket (LBP). Here, we report the identification and characterization of a new RXRα transcriptional antagonist by using structure-based virtual screening. The new antagonist binds with submicromol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Recently, by employing a docking-based virtual screening approach, we identified some small molecules that bind to the coregulator-binding surface of RXRα, a region where the binding sites of the corepressor and the coactivator overlap ( Figure 4A). One of the identified binders, 23, can regulate the biological functions of tRXRα, including inhibition of TNFα-induced interaction of tRXRα with p85α, inhibition of AKT activation in vitro and in animals, and induction of apoptosis [56] . Compound 23 doesn't bind to the LBP and represents the first example of an RXRα modulator that acts via the coregulator-binding site rather than the classical ligandbinding pocket.…”
Section: Novel Surface Binding Sites Of Rxrα As Alternate Sites For Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, by employing a docking-based virtual screening approach, we identified some small molecules that bind to the coregulator-binding surface of RXRα, a region where the binding sites of the corepressor and the coactivator overlap ( Figure 4A). One of the identified binders, 23, can regulate the biological functions of tRXRα, including inhibition of TNFα-induced interaction of tRXRα with p85α, inhibition of AKT activation in vitro and in animals, and induction of apoptosis [56] . Compound 23 doesn't bind to the LBP and represents the first example of an RXRα modulator that acts via the coregulator-binding site rather than the classical ligandbinding pocket.…”
Section: Novel Surface Binding Sites Of Rxrα As Alternate Sites For Tmentioning
confidence: 99%
“…Thus, there is an urgent need to dissect RXRα signaling pathways and to identify and develop new RXRα modulators that have unique properties and improved therapeutic indexes. In this review, we focus on the nongenomic activity of RXRα and highlight recent advances in this field with an emphasis on tRXRα actions [21] and RXRα modulation by targeting alternate binding sites on its surface [56,57] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that RXRα binding to PML/RARα is absolutely required for the development of acute promeylocytic leukemia (APL) in transgenic mice [53][54][55], demonstrating the oncogenic potential of this protein when it acts inappropriately. Several groups have demonstrated that RXRα is proteolytically cleaved in cancer cells [23,45,51,[56][57][58][59][60], and our illustration that tRXRα could enhance TNFα activation of PI3K/AKT and NF-κB pathways revealed that aberration in RXRα signaling by limited proteolysis plays an active role in cancer development [28,29,[61][62][63][64][65].…”
Section: Rxrα and Cancermentioning
confidence: 56%
“…3), could regulate the biological functions of tRXRα. Compound 23 could inhibit the TNFα-induced interaction between tRXRα and p85α, inhibit AKT activation in vitro and in animals, and induce apoptosis [61]. Compound 23 represents the first example of an RXRα modulator that acts via the co-regulator-binding site rather than the classical LBP.…”
Section: Ligands Targeting the Co-regulator-binding Site Of Trxrαmentioning
confidence: 99%
“…Among these, the co-regulator-binding site is the most studied. Recently, by employing a docking-based virtual screening approach, Chen et al identified a new RXRα antagonist, named compound 23, which can target the co-regulator-binding site of RXRα [ 77 ]. The compound does not bind to the ligand-binding pocket but to a hydrophobic groove on the surface of RXRα, a region where the binding sites of co-repressor and co-activator overlap [ 77 ].…”
Section: Different Binding Sites Of Rxrα For Drug Targetingmentioning
confidence: 99%